A dream denied: incarceration, recidivism, and young minority men in America - Soyer, Michaela (University of California Press, 2016)
"'A Dream Denied' shows how the narrative of American Dream shapes the offending trajectories of twenty-three young Latino and African American men in Boston and Chicago. Believing in the American Dream helps the teenagers to cope with the pains of incarceration. However, without the ability to experience themselves as creative actors, reproducing the rhetoric of American meritocracy leaves the teenagers unprepared to negotiate the complex and frustrating process of desistance and reentry